Some convergence and stability results for two new Kirk and Jungck-multi step type iterative processes - RamÃrez Juárez, Mauricio; Bezanilla López, Arnoldo (International Journal of Applied Mathematical Research, 2015)
In this work two new iterative processes called the â€œJungck-Kirk generalized multi-stepâ€ and â€œJungck-Kirk multi-stepâ€ are introduced and some convergence and stability results are proved for these iterative process. The results include results of almost stability and summable almost stability. Since these new iterative processes are more general than other ones extant in literature, some results of this work partially generalize results already proved in the existing literature.